2018
DOI: 10.1038/s41467-018-07711-y
|View full text |Cite
|
Sign up to set email alerts
|

Lithium hexamethyldisilazide initiated superfast ring opening polymerization of alpha-amino acid N-carboxyanhydrides

Abstract: Polypeptides have broad applications and can be prepared via ring-opening polymerization of α-amino acid N-carboxyanhydrides (NCAs). Conventional initiators, such as primary amines, give slow NCA polymerization, which requires multiple days to reach completion and can result in substantial side reactions, especially for very reactive NCAs. Moreover, current NCA polymerizations are very sensitive to moisture and must typically be conducted in a glove box. Here we show that lithium hexamethyldisilazide (LiHMDS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(129 citation statements)
references
References 68 publications
(42 reference statements)
1
128
0
Order By: Relevance
“…After the 2-h polymerization in DCM, the end-group analysis showed <1% loss of terminal amine groups 19 , indicating negligible chain termination 10,12 . In addition, owing to the fast polymerization kinetics and the water-immiscibility of DCM 20,21 , the polymerization of NCA in DCM in the presence of 10 vol% water still resulted in well-defined polypeptide with predictable MW, similar to that obtained under anhydrous conditions (Fig. 2d and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 57%
“…After the 2-h polymerization in DCM, the end-group analysis showed <1% loss of terminal amine groups 19 , indicating negligible chain termination 10,12 . In addition, owing to the fast polymerization kinetics and the water-immiscibility of DCM 20,21 , the polymerization of NCA in DCM in the presence of 10 vol% water still resulted in well-defined polypeptide with predictable MW, similar to that obtained under anhydrous conditions (Fig. 2d and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 57%
“…demonstrated that removal of CO 2 by a N 2 flow during polymerization of γ‐benzyl‐ l ‐glutamate N ‐carboxyanhydrides (BLG‐NCA) produced polypeptides with predictable molar masses and narrow distributions . Similar advances are achieved using ultrafast new ROP initiators, such as triethylaminetriamine (TREN) or LiHMDS . The latter initiator is particularly suitable as the polymerization is performed in an open‐air vessel despite NCA moisture sensitivity .…”
Section: Methodsmentioning
confidence: 95%
“…Similar advances are achieved using ultrafast new ROP initiators, such as triethylaminetriamine (TREN) or LiHMDS . The latter initiator is particularly suitable as the polymerization is performed in an open‐air vessel despite NCA moisture sensitivity . Finally, Cheng et al.…”
Section: Methodsmentioning
confidence: 96%
“…Polypeptides are widely used in the fields of life science and biomaterials owing to their superior biocompatibility and diversified functions. [ 282,283 ] In recent decades, peptides with antifouling properties have also been discovered and used for sundry applications such as biosensors. [ 242 ] Woll et al.…”
Section: New Materials To Resist the Fbrmentioning
confidence: 99%